High local recurrence of early-stage hepatocellular carcinoma after percutaneous thermal ablation in routine clinical practice. Issue 3 (March 2015) - Chinnaratha, Mohamed A.; Sathananthan, Dharshan; Pateria, Puraskar; Tse, Edmund; MacQuillan, Gerry; Mosel, Leigh; Pathi, Ramon; Madigan, Dan; Wigg, Alan J.
Abstract : Background and aim: The risk of local tumour progression (LTP) and factors predicting LTP following percutaneous thermal ablation (PTA) of early-stage hepatocellular carcinoma (HCC) have not been well studied in non-trial settings and may be underestimated. We aimed to assess these outcomes in a multicentre study. Patients and methods: This was a retrospective review of consecutive patients with early-stage HCC treated with a curative intent across three tertiary Australian centres between 2006 and 2012 with either radiofrequency ablation or microwave ablation. The primary endpoint was LTP and multivariate analysis was carried out to identify the independent predictors of LTP. Results: In total 145 HCC nodules were treated in 126 patients (78% men, mean±SD age 62±10 years) with a mean±SD follow-up of 13.5±13 months. Local recurrence was observed in 23.4% (34/145). Mean±SD LTP-free survival was 46.9±3.6 months. For HCC nodules 2 cm or less, local recurrence rates were lower (15.9%), with a mean±SD LTP-free survival of 48.8±4.2 months. Poorly differentiated HCC [hazard ratio (95% confidence interval)=4.8 (1.1–20.4), P =0.032] and pretreatment α-fetoprotein more than 50 kIU/l [8.2 (1.7–39.0), P =0.008] were independent predictors of LTP. LTP rates were not significantly different between the radiofrequency ablation and the microwave ablation groups (22.8 vs. 25.8%, P =0.7). There were six (4.8%) procedure-related adverse events, but no deaths. Conclusion: Local recurrence after PTA for early-stage HCC is high in routine clinical practice. Poorly differentiated HCC and pretreatment α-fetoprotein are important, independent predictors of LTP. Further well-designed randomized controlled trials with larger sample sizes using adjuvant therapies in combination with PTA to decrease LTP rates are warranted.